Multifunctional, Biocompatible, Non‐peptidic Hydrogels: from Water Purification to Drug Delivery. Issue 8 (8th June 2016) - Baker, Benjamin C.; Higgins, Clare L.; Ravishankar, Divyashree; Colquhoun, Howard M.; Stevens, Gary C.; Greco, Francesca; Greenland, Barnaby W.; Hayes, Wayne
Abstract: A novel series of low molecular weight non‐peptidic, biocompatible super‐hydrogelators with both water purification and drug delivery properties have been developed. Linking the bis aromatic urea groups responsible for gelation together to form bi‐ and tri‐armed gelators, affords good control over gelation and water purification properties. The use of the gels as effective drug scavengers and delivery systems has been demonstrated with dye substrates, via pH inversion, as monitored by UV‐vis spectroscopy. Finally, the systems′ abilities as both drug scavenging and delivery systems have been demonstrated with the clinically‐approved drugs chlorpromazine and doxorubicin, respectively. Abstract : Herein we describe the synthesis and properties of three generations of low molecular weight non‐peptidic super hydrogelators. These non‐cytotoxic super hydrogelators exhibit both water purification and drug delivery properties via the controlled uptake of aromatic based dyes and release of the clinically‐approved drugs chlorpromazine and doxorubicin.